Evaluation and the english teaching learning process with the students of 1st, 2nd and 3rd years of bachillerato at unidad educativa anexa a la Universidad Nacional De Loja. Academic year 2012 -2013 - Guayllas Sarango, Norma Isabel (2014)
The present research work entitled: “EVALUATION AND THE ENGLISH TEACHING LEARNING PROCESS WITH THE STUDENTS OF 1st, 2nd and 3rd YEARS OF BACHILLERATO AT “UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA”. ACADEMIC YEAR 2012 -2013” has been done with the purpose of analyzing the types of evaluation that teachers apply in the English teaching-learning process. In order to carry out every part of this research work, the following methods were employed: scientific, analytical-synthetic, explicative, descriptive and statistic. Moreover, the survey technique was used to collect information which was applied to 5 English teachers and 100 students of the researched institution being done in June 2012. The results showed that both formative and summative evaluation are the most applied by teachers, while initial evaluation use is limited which doesn’t permit to determine previous students’ knowledge, skills and their learning needs at the beginning of the academic year.